2005
DOI: 10.1017/s0272263105050175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acoustic Variability on Second Language Vocabulary Learning

Abstract: This study examined the effects of acoustic variability on second language vocabulary learning. English native speakers learned new words in Spanish. Exposure frequency to the words was constant. Dependent measures were accuracy and latency of picture-to-Spanish and Spanish-to-English recall. Experiment 1 compared presentation formats of neutral (conversational) voice only, three voice types, and six voice types. No significant differences emerged. Experiment 2 compared presentation formats of one speaker, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
147
11
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(188 citation statements)
references
References 21 publications
23
147
11
3
Order By: Relevance
“…A large literature on phonological contrast learning has shown that training environments with high acoustic-phonetic stimulus variability, which expose learners to a wide variety of exemplars of the feature or contrast to be learned, result in more robust representations of the learned features, thus improving generalization to novel stimuli in addition to enhancing learning of the trained stimulus set (Lively et al, 1993;Clopper and Pisoni, 2004;Barcroft and Sommers, 2005). Similar results have been observed in morphosyntactic learning (Brooks et al, 2006).…”
Section: Introductionsupporting
confidence: 58%
“…A large literature on phonological contrast learning has shown that training environments with high acoustic-phonetic stimulus variability, which expose learners to a wide variety of exemplars of the feature or contrast to be learned, result in more robust representations of the learned features, thus improving generalization to novel stimuli in addition to enhancing learning of the trained stimulus set (Lively et al, 1993;Clopper and Pisoni, 2004;Barcroft and Sommers, 2005). Similar results have been observed in morphosyntactic learning (Brooks et al, 2006).…”
Section: Introductionsupporting
confidence: 58%
“…We found few examples of such article types (e.g., Barcroft & Sommers, 2005;Marsden et al, 2013) and they were not included in our current synthesis because we investigated replications of studies in different publications. Current limitations on article length are probably one reason why this was rare, but we are hopeful that this situation will change as publishers remove formal word limits as publication moves online (though to the best of our knowledge, only Wiley-Blackwell has yet done this).…”
Section: Cultural and Procedural Changes In Publishingmentioning
confidence: 99%
“…These results suggest that a simple slowing in speaking rate should not pose a significant challenge for native listeners. However, variability within the signal has also been shown to have both negative (Barcroft and Sommers, 2005) and positive (Baese-Berk et al, 2013;Barcroft and Sommers, 2005;Bradlow and Bent, 2008;Sommers and Barcroft, 2007) effects on speech perception and learning. Variability in speaking rate, in particular, has been shown to hinder speech perception (Sommers et al, 1994), and word identification (Barcroft and Sommers, 2005;cf.…”
Section: Introductionmentioning
confidence: 99%